Water film in very high humidity inhibits mold growth on the damp surface of soil ruins. (15th August 2020) - Li, Yonghui; Wu, Ruobin; Xie, Huarong; Zhao, Guoli; Dang, Xinyuan; Hokoi, Shuichi
Abstract: Mold growth, one of the most severe hazards to soil ruins in humid regions, is often caused by a favorable hygrothermal environment, that is, high relative air humidity (RH) with a suitable temperature and other environmental variables. It was reported that no mold growth occurs in buildings when RH is less than 70%, and mold grows more easily and quickly as humidity increases (Sedlbauer, 2001). The characteristics of mold growth under extremely high humidity conditions remain elusive. In our previous research, samples from the Wenzhou Qiaolou soil ruin were used to estimate the effects of ventilation and lighting modes on mold growth. On that basis, subsequent experiments and analysis were conducted to assess the relationship between mold growth, and RH and lighting modes. In the experiments, six sets of initially wet samples were placed in artificial lighting or dark conditions with different RH to evaluate the characteristics of mold growth under extremely high humidity conditions. We found that extremely high humidity with a condensation environment had a significantly inhibitory effect on mold growth compared with the humidity range (94%–99%) favorable for it. Observations with the microscope conducted to understand the moisture condition of the sample surface confirmed a possibility that the reduction or isolation of oxygen under very high RH conditions with condensation caused this result. This paper provides basic knowledge regarding the characteristics of mold growth in an extremely high humidity environment, and is practically useful for methods of inhibition of mold growth in a high-humidity environment. Highlights: Experiment aimed to observe mold growth on soil ruins of high-humidity environment. The humidity fluctuation near the surface of soil ruins promote massive mold growth. Extremely high-humidity with repeated condensation environment inhibits mold growth. The formation of a water film may cut off the oxygen supply to mold. Raising RH to a very high-humidity may be an alternative conservation of heritages.